Sistem Pendukung Keputusan Penerimaan Dosen Tetap Menggunakan Fuzzy-Analytic Hierarchy Process - Made Agung Raharja; I.N Anom Cahyadi Putra (LPPM Universitas Dhyana Pura, 2015)
A decision is one problem facing almost every day, even every moment. This research will combine the capabilities of Logic Samar (Fuzzy Logic) with the Analytic Hierarchy Process (AHP-F). Use application with Fuzzy-AHP method is still rarely used or methods that are new in the making of a decision support system for Fuzzy AHP makes the problem a broad and unstructured become a model that is flexible and easy to understand.Decision Support System Acceptance Lecturers Using Fuzzy-Analytic Hierarchy Process (AHP-F). (Case Study: University of Dhyana Pura Bali), it can be concluded as follows: Knowing what the user needs in a decision support system acceptance tenured faculty. The screening decision support system of filing of lecturers using fuzzy AHP method at the University of Dhyana Pura consists of several stages. First, create the structure. Furthermore, determining the value of fuzzy synthesis (Si) priorities, determine the value of the vector (V) and the ordinate value defuzzification (d '). Calculating normalized values fuzzy weight vector (W) equal to the weight of global priorities. With Fuzzy AHP, form a decision support system that can select prospective teachers, and determine who deserves and is entitled to be accepted as a lecturer at the University of Dhyana Pura. Keywords: DSS, Fuzzy-Analytic Hierarchy Process (F-AHP)